Evaluating Indonesia's Policy Framework for Protecting Migrant Workers A Human Rights-Based Diplomatic Approach - Kananita Saras Anggitadewi Saras; Anang Puji Utama; Herlina Juni Risma Saragih; Rachmat Setiawibawa; Arifuddin Uksan (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2026)
This study evaluates the policy framework adopted by Indonesia in safeguarding the rights and welfare of its migrant workers through the lens of human rights-based diplomacy. The inquiry is motivated by the persistent vulnerability of Indonesian migrant workers to various forms of exploitation, including labor abuse, wage theft, contract violations, and human trafficking, despite the considerable economic contributions these workers make through remittance flows to national development. Employing a descriptive-analytical literature review methodology, this research draws on peer-reviewed academic journals, official documents from international organizations, national legislation, and relevant studies in the fields of migration governance and protective diplomacy. The analytical framework integrates three theoretical pillars: the rights-based approach, consular and protective diplomacy theory, and the concept of human security. Findings reveal that Indonesia has undergone a significant paradigm shift in its migration governance, most notably through the enactment of Law Number 18 of 2017, which repositions migrant workers as rights-bearing subjects entitled to comprehensive state protection across all phases of the migration cycle. Additionally, Indonesia has engaged in progressively active bilateral, regional, and multilateral diplomacy to elevate the standards of migrant worker protection in destination countries. Nevertheless, structural challenges persist, including interagency coordination deficits, high rates of non-procedural placement, limited protective capacity in overseas diplomatic missions, and an imbalanced bargaining position relative to receiving states. At the regional and global levels, Indonesian diplomacy continues to encounter constraints arising from the predominantly non-binding character of most international instruments. The study concludes that effective migrant worker protection necessitates deeper integration between domestic policy and multi-level, rights-based diplomacy. Strengthening institutional capacity, harmonizing regulatory frameworks, and optimizing coalition-based diplomacy represent the most strategic pathways toward enhancing the effectiveness of Indonesia's international migrant protection regime.